2020
DOI: 10.1016/j.rboe.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Associação dos polimorfismos ESRα XbaI A > G, ESRα PvuII T > C e ESRβ AlwNI T > C com o risco de desenvolver escoliose idiopática da adolescência: Revisão sistemática e metanálise genética

Abstract: ResumoVários estudos de associação entre os polimorfismos genéticos nos receptores α e β de estrogênio e a escoliose idiopática da adolescência (EIA) foram publicados nas últimas duas décadas. No entanto, a associação com a EIA, especialmente em diferentes subgrupos étnicos, continua a ser controversa. Assim, o presente estudo investigou esses dados inconclusivos por meio de uma metanálise para avaliar sistematicamente essa associação.Uma pesquisa bibliográfica foi realizada nas bases de dados PubMed, ISI Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Osteoarthritis (OA) is a progressive and irreversible degenerative condition, that affecting synovial joints, most frequently the knees, hips, hands, and spine. [1][2][3] OA, one of the most common causes of disability, affects more than 100 million people worldwide. 4 , 5 Radiological studies revealed that more than 20 million people in the US suffer from knee OA.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a progressive and irreversible degenerative condition, that affecting synovial joints, most frequently the knees, hips, hands, and spine. [1][2][3] OA, one of the most common causes of disability, affects more than 100 million people worldwide. 4 , 5 Radiological studies revealed that more than 20 million people in the US suffer from knee OA.…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity and publication bias are of importance which may affect the results of meta-analysis [ 44 , 70 , 42 , 71 , 72 ]. In the current meta-analysis, a significant heterogeneity existed for -819T>C and -1082A>G polymorphisms under almost genetic models in overall, but not for IL-10 -592A>C. After subgroup analyses by ethnicity, the heterogeneity was not decreased by ethnicity, suggesting that other factors such as gene-environment factors or histological type cause the heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis performed by Sobhan et al suggested that ESR1 polymorphisms rs9340799 and rs2234693 are not related to the risk of IS occurrence. However, rs9340799 may be associated with the risk of developing AIS among the Asian population [47]. Due to the unknown role of estrogens and their receptors in IS etiology, we evaluated the gene methylation status of estrogen receptors in IS.…”
Section: Discussionmentioning
confidence: 99%